Spatial mapping of groundwater quality using GIS for Jakham River basin of Southern Rajasthan - Vinay Kumar Gautam; Mahesh Kothari; Pradeep Kumar Singh; Sita Ram Bhakar; Kamal Kishore Yadav (Environment Conservation Journal, 2022)
The physico-chemical analysis of groundwater quality plays a significant role to manage the water resources for drinking as well as irrigation in the sub-humid and semi-arid agro-climatic areas. In this study, the hydrogeochemical analyses and spatial mapping of groundwater quality in the Jakham River Basin located in the southern part of Rajasthan were investigated.The groundwater quality samples were collected from 76 wells marked on the grid map of 5×5 km2 area.A spatial distribution in sampling location in the basin was prepared using GIS (Geographical information system) tool based on 6 physico-chemical parameters i.e., pH, EC, TDS, Cl, NO3and F.The groundwater quality data from the pre and post-monsoon seasons of 2019-20 were used to carry out a detailed analysis of water quality parameters.The water quality maps for the entire basin have been generated using anIDW interpolation technique for these parameters as per the identified location.The higher value of TDS and EC were found in the south-eastern part and along the roadside of study area, which were dominated by agriculture activities and industrial influence. The concentration was observed higher in the post-monsoon period. For EC and TDS, major part of the (>50%) of the study area comes under the safe limit of potable water. Major part of the basin witnessed fluoride concentration (0.40-80 mg/l) for both the season, which is lower than the permissible limit. Higher NO3 concentration was observed after the rainy season. The influence of geogenic activities could be clearly seen in the groundwater quality of the basin. Theresultant map shows that the entire basin has optimally goodgroundwater quality for human consumption. Hence, this study provides suggestion to prepare strategies for the proper management and augmentation of the groundwater condition in the Jakham River Basin.